Drawing and Coloring Using Crayon with Gradation Technique at Kindergarten - Rizki Sevi Triana; Joko Pamungkas (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
As an Early Childhood Education teacher, you are required to be able to understand the world of art and develop interesting art lessons for children. This research was conducted to understand the process of learning art to students at the Institute. By using this type of qualitative descriptive research, the researcher will examine the facts in the field with detailed interpretations. Data collection techniques using observation, documentation, and interviews. The data analysis uses data collection, data reduction, data display, verification, and affirmation of conclusions. The research proves that the results of introducing art learning concepts to students through drawing and coloring activities using gradation techniques using crayon at kindergarten in Jember can be developed well. From the results of this study, it has a positive impact on students and is beneficial for developing their faith, honing their talents, and creativity to be even more enthusiastic in the art learning process.